Fluoride regulates chondrocyte proliferation and autophagy via PI3K/AKT/mTOR signaling pathway. (1st November 2021) - Ma, Lan; Zhang, Ruixue; Li, Demin; Qiao, Tingting; Guo, Xiaoying
Abstract: Fluorine is an essential trace element for human health. However, excessive fluoride intake causes skeletal fluorosis which affects cartilage development. Fluoride inhibited chondrocyte proliferation which is the initial and critical step of endochondral ossification, but the underlying mechanism has not been clearly illustrated. Mammalian target of rapamycin (mTOR) is an important protein kinase which modulates various cellular processes and is believed to be a central regulator of chondrocyte proliferation and autophagy. In this study, we explored the effect of fluoride on the proliferation and autophagy of chondrocytes and the regulatory role of mTOR signaling pathway. Our results suggested that NaF inhibited the protein expressions of proliferating cell nuclear antigen (PCNA) and pS6 in cultured fetal rat tibias. Furthermore, NaF significantly downregulated the expressions of mTOR signaling pathway-related genes, including PI3K, AKT, mTOR, 4EBP1 and S6K1 in mouse ATDC5 chondrogenic cell line. We also found that NaF increased autophagy in ATDC5 cells. The mRNA and protein levels of autophagy-related genes LC3, Beclin1 and p62 were significantly changed after NaF treatment. Further studies demonstrated that MHY1485, a small-molecular mTOR activator, totally reversed fluoride-induced promotion of autophagy. MHY1485 also recovered the downregulation of proliferative chondrocytes markers Sox9 and Type Ⅱ Collagen ( Col2a1 ) induced by fluoride in ATDC5 cells . Taken together, our result demonstrate that fluoride suppressed proliferation and facilitated autophagy via PI3K/AKT/mTOR signaling pathway in chondrogenesis. Highlights: Fluoride inhibited chondrocyte proliferation. Fluoride increased autophagy in ATDC5 cells. Fluoride inhibited PI3K/AKT/mTOR signaling pathway. Fluoride-induced adverse effects were mediated by PI3K/AKT/mTOR signaling pathway.